Penerimaan Siswa Sekolah Berbasis Jarak Menggunakan Algoritma Haversine - Dani Yusuf; Hendarman Lubis; Uus Rusmawan (Journal of Information System, Applied, Management, Accounting and Research, 2026)
New student admission is a critical process in the education system that requires fairness, objectivity, and transparency, particularly in domicile-based selection mechanisms. This study aims to design and implement a distance-based student admission system using the Haversine algorithm at SMK Metland Cibitung. The research method applies an applied quantitative approach with a system development framework utilizing geographic coordinate data (latitude and longitude) to calculate the distance between applicants’ residences and the school location. The Haversine algorithm is used to compute distances based on the great-circle distance concept, providing higher accuracy compared to conventional estimation-based approaches. The results show that the system is able to automatically calculate distances and rank applicants based on proximity with consistent outcomes. The implementation improves selection efficiency and supports the principles of objectivity and transparency in the Student Admission System (SPMB). Therefore, the Haversine algorithm is an effective solution for developing a distance-based student admission system.